Synthesis, characterization, and performance evaluation of PES/EDA-functionalized TiO2 mixed matrix membranes for CO2/CH4 separation - Eltahir Mustafa, S.G.E. (John Wiley and Sons Inc., 2017)
Poor adhesion between hydrophobic polymers and hydrophilic inorganic fillers is a challenge that encumbers a high separation performance of mixed matrix membrane (MMM). In this study, Titanium(IV) oxide (TiO2) nanoparticles were functionalized using ethylenediamine (EDA) before embedment in poly(ether sulfone) (PES) polymer matrix. MMMs were synthesized through dry phase inversion technique. Membranes morphology and nanoparticles dispersion was drastically enhanced posterior amine modification indicating an improved adhesion between the polymer and filler particles. Membranes thermal stability was likewise improved as higher degradation temperatures were perceived for PES/EDA–TiO2 MMMs. Gas separation evaluation for pure carbon dioxide (CO2) and methane (CH4) gases revealed a remarkably enhanced separation performance upon amine-grafting of TiO2 as EDA-TiO2 MMMs exhibited a higher separation performance as compared to MMMs with pristine TiO2. The highest ideal separation factor achieved was 41.52 with CO2 permeability of 10.11 Barrer at an optimum loading of 5 wt of EDA-TiO2 which is threefold higher as compared to neat PES membrane and approximately twofold higher than MMMs with pristine TiO2, respectively, at the same filler loading. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2017, 134, 45346. © 2017 Wiley Periodicals, Inc.